Discrete multifunctional sequence-defined oligomers with controlled chirality. Issue 24 (4th June 2020) - Li, Jie; Leclercq, Maxime; Fossepré, Mathieu; Surin, Mathieu; Glinel, Karine; Jonas, Alain M.; Fernandes, Antony E.
Abstract : New synthetic strategy leading to discrete poly(triazole-urethane) oligomers with a large range of functional side groups, programmable stereochemistry and sequentiality. Abstract : Discrete sequence-defined oligomers are synthetic mimics of short peptides, with possible applications in catalysis, information storage, drug delivery or self-assembly. Here, we report on the efficient and stereocontrolled synthesis of sequence-defined poly(triazole-urethane) oligomers incorporating a very large range of functional side groups, including alkyl, phenyl, pyridyl, hydroxyl, amine, imidazole and carboxylic acid functions. The route involves the alternation of chloroformate-mediated carbamate bond formation and Cu-catalyzed azide–alkyne cycloaddition reactions, expeditiously leading to oligomers up to octamers by an iterative exponential growth strategy. Additionally, the chirality of the monomers is straightforwardly controlled and maintained during the elongation process, leading to optically-active multifunctional oligomers of controlled molecular configuration, as confirmed by 1 H NMR, ESI-MS/MS and circular dichroism. Our strategy provides a versatile platform to efficiently synthesize discrete oligomers with programmable stereochemistry, sequentiality and multifunctionality.